The Effect of Peanut Skin Compost Mix Variaries on Planting Media on the Growth of Dendrobium Sp - Nur Rokhimah Hanik; Sri Harsono; Ratna Dewi Eskundari (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2021)
Ferns are a growing medium for orchids that are starting to be protected so that their availability is very limited and quite expensive, therefore a solution is needed to reduce maintenance costs by utilizing peanut shell compost as a mixture of media. Peanut shell compost can act as a medium and fertilizer. The purpose of this study is: 1. To determine the effect of various peanut shell compost mixtures in growing media on Dendrobium orchid growth. 2. To determine the best composition of peanut shell compost mixture for Dendrobium orchid growth. The results of this study serve as information material for Dendrobium orchid collectors and entrepreneurs about the effect of various peanut shell compost mixtures in growing media on the growth of Dendrobium orchids, as well as a reference material for further research related to efforts to improve Dendrobium orchid cultivation, especially the use of peanut shells as a medium. Grow as well as compost to increase the growth of Dendrobium orchids. The research period was started from July 2020 to December 2020. The research object was a 12 month old Dendrobium orchid, the research location was in Gabahan RT 05 RW 12 Jombor Bendosari Sukoharjo. Simple randomized research design with four treatments. Treatment A / K.0 of fern growing media without peanut shell compost, treatment B / K.1 / 2 of fern media mixed with compost with a ratio of 1: 1, treatment C / K.1 / 3 media fern mixed with peanut shell compost with a ratio 2/3: 1/3, and treatment C / K.1 / 4 media of fern mixed with peanut shell compost in the ratio 3/4: 1/4. Data were measured after 12 weeks from planting. Data analysis with Variance Test (Anava test) and advanced Duncan Multiple Range Test (DMRT).ÃÂ From the research it can be concluded that the variation of the peanut shell compost mixture in the growing medium has a significant effect on the growth of Dendrobium orchids on four (4) observed growth parameters (Leaf Length, Number of Leaves, Leaf Area, and Wet Weight. Moderate for the Number of tillers. There was a difference in effect, although this difference was not significant. And the treatment of compost mixture B / K.1 / 2 or with a ratio of 1: 1 gave the best effect on all observed growth parameters (Leaf Length, Number of Leaves, Leaf Area, Number of Tillers, and Gross weight. There is still a need to develop further research on peanut shell compost as a mixture for growing media, because in addition to reducing costs for growing media it can also reduce costs for purchasing fertilizer, because peanut shell compost contains a lot of N, P, and K elements. soil on growing media can reduce maintenance costs.